Fruit, fodder and fuel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Masau fruit or ber (Ziziphus mauritiana) is no stranger in many ACP countries. The tree is believed to originate from south Asia, but can be found throughout Africa, and in the Caribbean on Barbados, Guadeloupe, Jamaica and Martinique. Despite its...